Benzo[a]pyrene-Induced Developmental Toxicity in Caenorhabditis elegans: Potential Involvement of Insulin/IGF Signaling and Collagen Gene Dysregulation - Jinjin Zhou; Yage Shi; Yanfeng Zhou; Yang Ge (Toxics)
Benzo[a]pyrene (B[a]P) is a widespread and persistent organic pollutant that poses serious threats to human health. Although its carcinogenic properties have been extensively studied, its developmental toxicity and underlying mechanisms remain poorly understood. In this study, we employed Caenorhabditis elegans (C. elegans) as a model organism to investigate the effects of B[a]P exposure during early developmental stages. To comprehensively assess B[a]P-induced developmental toxicity, we employed high-throughput sequencing along with transgenic and mutant C. elegans strains. Exposure to B[a]P at concentrations exceeding 1 mg/L significantly reduced larval body size, decreased the number of adult worms, and delayed larval-to-adult development. Furthermore, we analyzed the expression of genes involved in cuticle collagen synthesis and key components of the insulin/insulin-like growth factor signaling (IIS) pathway, including daf-2 and daf-16. These findings suggest that B[a]P-induced developmental toxicity may be associated with dysregulation of the IIS pathway. Specifically, B[a]P appears to influence the activity of the downstream transcription factor daf-16, thereby altering the expression of collagen-related genes. This disruption in collagen synthesis may contribute to delayed larval development and impaired maturation. Our study provides new insights into the environmental hazards associated with B[a]P exposure and reveals a potential mechanism underlying its developmental toxicity. Moreover, our findings highlight the critical role of collagen gene regulation during early developmental stages. These genes may serve as potential biomarkers for environmental toxicant exposure, particularly in vulnerable populations such as children undergoing critical periods of development.